Morphometry and displacement analysis of the upper lips following maxillary full-arch implant-supported fixed prostheses: a 3D morphometric study - Keyi Hao; Jia Luo; Ping Di; Yu Zhang; Ye Lin (BMC, 2021)
Abstract Background With the emergence of three-dimensional (3D) integration technology, analysis of soft tissue displacement and morphological changes after maxillary full-arch implant-supported fixed prostheses can be performed. The aim of this study was to verify the feasibility of the 3D integration method for constructing the relative position of the prostheses and facial soft tissue, evaluate the displacement and morphological variation of the upper lips after maxillary full-arch implant-supported fixed prostheses. Methods Twenty-five maxillary edentulous patients were recruited in this study. At the time of final prosthesis delivery, the 3D prostheses data and three 3D facial profiles were integrated. After method validation, the 3D position changes of seven soft tissue landmarks were used to reflect the 25 upper lips. The variation of four morphological distances were analyzed to reflect the morphological alteration of the upper lips. Two pairs of dentofacial landmarks were used to analyze the sagittal relative position of the prostheses and soft tissue. The included patients were also grouped to determine the impact of sex, upper lip thickness, and length on lip support changes. Results The average distance of the two matched relative reliable forehead regions was only 0.32 mm. The sagittal shifts of labrale superius (LS), stomion (STO), crista philtri left (CPHL) and crista philtri right (CPHR) were 3.44 ± 1.39 mm, 2.52 ± 1.38 mm, 3.04 ± 1.18 mm, and 3.12 ± 1.21 mm, respectively. With the exception of the decrease in the length of subnasale (SN)-LS, the length of cheilion right (CHR)-cheilion left (CHL), CPHR-CPHL, and LS-STO significantly increased. The two pairs of dentofacial landmarks had strong positive movement correlations along the sagittal direction. Patients with thinner and longer lips showed more lip support than those with thicker and shorter lips by a clinically insignificant amount. Conclusions The integration method of 3D facial and dental data showed high repeatability in constructing the dentofacial relative position. The linear equations reflecting dentofacial relative position could aid clinicians in evaluating the restoration effect and estimate the upper lip variation.